Vacinas em forma inativada e atenuada contra vírus influenza induzem diferente resposta celular imune e perfil de expressão gênica em crianças - Cao, Raquel Giacomelli (2013)
INTRODUCTION: Studies have shown that LAIV is more effective than TIV for prevention of influenza infection in young children, but the underlying mechanisms associated with protection are still not well defined. OBJECTIVES: To assess differences in cellular immunity and gene expression profiles in children after immunization with LAIV or TIV. METHODS: Peripheral blood of previously healthy children was collected pre and postvaccination and analyzed for B cells measurement and antibodies production. Microarray analyses were applied to assess the gene expression profiles. RESULTS: LAIV vaccinees showed number of naïve, memory and transitional B cells increased on day 1 compared to baseline (p<0.05). TIV vaccinees showed the number of plasmablasts increased on day 7 post-vaccination (p≤0.01). In addition, the titers for the three strains of the vaccine (H1N1, H3N2 and B) were significantly elevated on the TIV group when compared with the LAIV group. Regarding the transcriptional profiles presented, both vaccines induced interferon signaling, but in different time points, TIV 1 day postvaccination and LAIV 7 days post-vaccination, the last only in children younger than 5 years old. CONCLUSIONS: These results indicate that LAIV and TIV induced different immune responses in peripheral blood of vaccinated children and that both vaccines induce interferon signaling post-vaccination.